A proprotein convertase subtilisin/kexin type 9 inhibitor provides comparable efficacy with lower detriment than statins on mitochondria of oxidative muscle of obese estrogen-deprived rats - Chanisa Thonusin (2020)
OBJECTIVES: The aim of the study was to compare the effects of atorvastatin, a proprotein convertase subtilisin/kexin type 9 inhibitor (PCSK9i), and 17β-estradiol on oxidative muscle mitochondria in a model of menopause with obesity. METHODS: Female Wistar rats consumed either a standard diet (n = 12) or a high-fat/calorie diet (HFCD: n = 60). At week 13, standard diet-fed rats underwent a sham operation, whereas HFCD-fed rats underwent either a sham operation (n = 12) or an ovariectomy (n = 48). At week 19, all sham-operated rats received vehicle, and ovariectomized HFCD-fed rats received either vehicle, 40 mg/kg/d of atorvastatin, 4 mg/kg/d of PCSK9i (SBC-115076), or 50 μg/kg/d of 17β-estradiol for 3 weeks (n = 12/group). Metabolic parameters and soleus muscle physiology were investigated at the end of week 21. RESULTS: Sham-operated and ovariectomized HFCD-fed rats developed obesity, hyperlipidemia, and insulin resistance, also showing increased oxidative phosphorylation (OXPHOS) proteins, ratio of p-Drp1-to-total Drp1 protein, malondialdehyde level, mitochondrial reactive oxygen species, and mitochondrial membrane depolarization in soleus muscle. All drugs equally decreased insulin resistance, OXPHOS proteins, ratio of p-Drp1-to-total Drp1 protein, and malondialdehyde level in soleus muscle. Only atorvastatin and PCSK9i attenuated hypertriglyceridemia, whereas 17β-estradiol had greater efficacy in preventing weight gain than the other two drugs. In addition, 17β-estradiol decreased mitochondrial reactive oxygen species and mitochondrial membrane depolarization. Atorvastatin increased ratio of cleaved caspase 3,8-to-procaspase 3,8, and cytochrome C. CONCLUSIONS: 17β-Estradiol exhibits the greatest efficacy on the attenuation of obesity with the least harmful effect on skeletal muscle in a model of menopause with obesity, yet its effect on the treatment of hyperlipidemia is inferior to those of standard lipid-lowering agents.